2020
DOI: 10.1002/anie.202011171
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Potential of Meroterpenoid Cyclases to Expand the Chemical Space of Fungal Meroterpenoids

Abstract: OpenBU http://open.bu.edu Chemistry BU Open Access Articles 2020-09-15 Exploiting the potential of meroterpenoid cyclases to expand the chemical space of fun...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…Later on, the Dickschat group [154] demonstrated that bacterial terpene synthases could cyclize methylated IPP analogues. Recently, Porco, Abe and coworkers [155] evaluated the substrate promiscuity of fungal meroterpenoid cyclases in the early structural diversity‐generating steps of fungal meroterpenoid biosynthetic pathways (Scheme 36b). Using this approach, 12 unnatural meroterpenoids were accessed chemoenzymatically from synthetic substrates.…”
Section: Complementary Methods/future Directionsmentioning
confidence: 99%
“…Later on, the Dickschat group [154] demonstrated that bacterial terpene synthases could cyclize methylated IPP analogues. Recently, Porco, Abe and coworkers [155] evaluated the substrate promiscuity of fungal meroterpenoid cyclases in the early structural diversity‐generating steps of fungal meroterpenoid biosynthetic pathways (Scheme 36b). Using this approach, 12 unnatural meroterpenoids were accessed chemoenzymatically from synthetic substrates.…”
Section: Complementary Methods/future Directionsmentioning
confidence: 99%
“…AndB, the dedicated non-canonical terpene cyclase from the and BGC, was shown to convert the unnatural DMOA-derived substrates 68 and 70 into the novel meroterpenoids 69 and 71, respectively, with 71 displaying an unprecedented 6,5,5,6-tetracyclic ring system. 87 The derived novel cyclase products will enable further downstream tailoring.…”
Section: Anditomin and Related Meroterpenoidsmentioning
confidence: 99%
“…In fact, the mutasynthetic studies with AndB were part of a larger study that investigated the potential of nine non-canonical meroterpenoid cyclases to convert unnatural substrate analogues, resulting in the formation of twelve novel meroterpenoids and emphasizing the power of this strategy to drive structural diversification of fungal meroterpenoids. 87…”
Section: Anditomin and Related Meroterpenoidsmentioning
confidence: 99%
“… 52 Abe, Porco, Tantillo, Fujita, et al used the same MOF to determine the structures of meroterpenoids chemoenzymatically synthesized using fungal meroterpenoid cyclases. 53 For mechanistic studies, Fujita et al used a variant of 1 to examine Pd-catalyzed aryl brominations via SC-XRD. 54 ZnI 2 , tpt, and a palladacycle (dibenzo[ f , h ]quinolinyl Pd(II) methylxanthate) were cocrystallized, and subsequent solvent exchange with MeCN provided a crystalline flask for time-course studies that involved soaking with N -bromosuccinimide.…”
Section: Diversity Of Crystalline Matricesmentioning
confidence: 99%